Pengaruh Pengetahuan Perpajakan, Sosialisasi Pajak Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Medan - Alyyatul Nisa Ragil Lesmana; Fazira Putri Natasya; Risma Abidah Nasution; Dini Vientiany (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The purpose of this study was to determine the effect of taxation knowledge, tax socialization and tax sanctions on compliance of MSME taxpayers in Medan. In this study, the research method used is quantitative method. The population of this study to MSME taxpayers in Medan amounted to 40 MSMEs. The sample will be randomly selected from the population to collect representative data. The results showed that the Sig value of the variable (X1) knowledge ˂ 0.05, then 0.005 ˂ 0.05. So it can be concluded that Hₐ1 is accepted and Hₒ1. is rejected. Variable (X2) Socialization ˂ 0.05 then 0.008 ˂ 0.05. So it can be concluded that Hₐ2 is accepted and Hₒ2 is rejected. Bariable (X3) Tax Sanctions ˂ 0.05 then 0.002 ˂ 0.05. So it can be concluded that Hₐ3 is accepted and Hₒ3 is rejected. This shows that knowledge has a significant effect on taxpayer compliance as variable Y positively. Simultaneously with the F test shows that Taxation Knowledge, tax socialization and Tax Sanctions have a significant effect on MSME Taxpayer Compliance in Medan Sig value ˂ 0.05 then 0.000 ˂ 0.05. So it can be concluded that in the F test Hₐ is accepted and Hₒ is rejected.